Technical Guideline for applying mechanization in straw management towards reducing greenhouse gas emissions and circular economy in agriculture - Nguyen Van Hung; Tran Thi Cam Nhung; Nguyen Van Hieu; Nguyen Thanh Nghi; Nguyen Thanh My; Tran Ngoc Thai; Pham Thi Minh Hieu; Tran Thi Kim Thuy; Le Nhut Tao; Tran Thi My Hanh; Nguyen Huu Diem Ha; Ngo Duc The; et al. (2023)
The technological guideline for the application of mechanization in rice straw management, with the goal of reducing greenhouse gas emissions and promoting a circular economy in agriculture, comprises two primary interventions: mechanized straw collection from fields and mechanized straw composting. Mechanized straw collection involves the introduction of technologies and mechanized options for collecting straw from both dry and wet fields. It includes the utilization of a self-propelled round baler capable of operating in both dry and wet fields, while a tractor-mounted round baler is suitable only for dry field conditions. On the other hand, mechanized straw composting is a technology designed to optimize the physical, chemical, and biological conditions involved in the rice straw composting process. This is achieved through the use of decomposing microorganisms, ensuring the maintenance of the optimal C/N ratio, temperature, and moisture content throughout the process. Regarding its scope and conditions of application, the guideline can be applied by all rice farmers and cooperatives in the Mekong River Delta provinces with similar conditions, provided they are equipped with the appropriate machines and equipment as specified in the guideline.